KRITIK HUKUM ISLAM TERHADAP PERUBAHAN UNDANG-UNDANG NOMOR 38 TAHUN 1999 TENTANG PENGELOLAAN ZAKAT - Ahmad Fathonih (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
Zakat is believed as part of Islamic legal doctrines. It means that Islam will never stand up without supported by zakat because it is also placed and mentioned in the Quran. As one of Islamic doctrines, the Quran describes the importance of zakat similar with praying shalat like quoted in the surah al-Baqarah verse 277. It is actually seemed that every Muslim needs to do shalat as a ritual activity and zakat is both ritual and social. This paper explains the position and function of zakat that is regulated under the law of zakat number 38 of 1999 as one of Islamic law instruments to increase the development of economy in Indonesia.